EVALUATION OF THE IMPLEMENTATION OF PUBLIC SERVICE STANDARDS IN PUBLIC ADMINISTRATION - Loso Judijanto; Al-Amin (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2025)
Public Service Standards are an important component in efforts to improve the quality of state administration. This research aims to evaluate the implementation of Public Service Standards in various government agencies. The method used includes a literature study. The evaluation results show that the implementation of these standards has brought improvements in terms of transparency and efficiency of public services. However, there are still some obstacles such as limited resources and differences in understanding among government officials. This research concludes that despite the progress, there is still a need for continuous efforts to optimise the implementation of the Public Service Standard.